Speaking in tongues, a text analysis of economic opinion at Newsweek, 1975-2007 - Tiago Mata; Claire Lemercier (Duke University, Center for the History of Political Economy (CHOPE), 2011)
Among American news magazines Newsweek holds the distinction of having hosted some of the most authoritative interpretation of economic events. Its cast of columnists included two of the most acclaimed academic economists and some of the most widely read business journalists of the late twentieth century. The purpose of this paper is to examine their writings as examples of "economic journalism". We used statistical methods to study word co-occurrences and identify vocabulary classes for bodies of texts for 1975-1990 and 1991-2007. We are thus able to distinguish two domains of discourse: political economy and the causal economy. We find traces of changes in economic discourse resulting from the end of the Cold War as well as point out differences in the language of academics and journalists.
Keywords: A11; B20; N01; 330; economic opinion; policy; economic journalism; text analysis; economic ontology